Largo da Estação Ferroviária de Cruz Alta: uma proposta de diretrizes para requalificação do espaço - Silveira Neto, Valdomiro (2022)
This study aimed to highlight public spaces and their uses in a city, the need to rethink these spaces and the potential to restructure them for leisure, socialization, citizens' well-being and tourist activity. It can be seen that the health crisis that occurred due to the covid-19 pandemic has exponentially increased people's demand for outdoor spaces with infrastructure for recreational activities, for the practice of sports, with accessibility and safety. In this scenario, the research had as general objective to analyze spatially a cut of the urban fabric of the city of Cruz Alta, in Rio Grande do Sul, located in Largo da Estação Ferroviária in order to propose urban requalification guidelines to alleviate the existing physical problems. Also analyze and understand the physical-spatial conformation of the defined area, propose guidelines for improving the space, promoting greater identity, socialization and comfort to users and adding value to the existing good with contemporary and quality possibilities. As for the methodological procedures, it is a qualitative/quantitative research developed in three stages: from the bibliographic review and survey of the state of the art of the theme and a SWOT analysis of the area and the building was also applied. From the results, a proposal with guidelines for urban requalification of Largo da Estação Ferroviária de Cruz Alta, RS, is presented as a final product, reinforcing the potential for offering a qualified space for leisure and well-being of the community.